Bank performance during the COVID-19 pandemic: Does income diversification help? - Tin H. Ho; Nguyen Dat; Thu B. Luu; Tu D. Q. Le; Thanh D. Ngo (Journal of Applied Economics, 2023)
The Covid-19 pandemic's economic effect led to tighter credit standards and a decline in the market for many types of loans. With a rich database of 1,231 banks in 90 countries from 2018Q1 to 2021Q4, we conducted a timely, broad-based international study to investigate whether non-interest activities, serving as a shock absorber, can promote bank performance before and during the Covid-19 pandemic. When using a dynamic panel data model with a system GMM estimator, our findings indicate that banks should be encouraged to diversify their income sources to reduce the adverse effects of the shock. With comparative analysis, we also found heterogeneous effects of income diversification on bank performance by its components, in pre-Covid-19 and during-Covid-19 periods, in both developed and developing countries. This study implies that bank managers should diversify income sources, especially fee-based services, trading activities, and foreign currency, to foster financial performance and stability during exogenous shocks.
Keywords: 330; Covid-19; Diversification; Profitability; Risk-taking